Paul's and the Position of Women in Worship Service: Study of 1 Timothy 2:8-15 - Tampilang, Risno; Letunggamu, Feyby Chaeren; Manambe, Christian Yafet (Evangelikal: Jurnal Teologi Injili dan Pembinaan Warga Jemaat, 2024)
The dichotomy that is often debated is patriarchal and feminist cultural systems. The centralization of human life is largely directed towards men, both in social and religious circles, thereby encouraging the objectification of women and dominating them. The space for women seems to be closed, this also happens in the Christian sphere, where there are still churches that adhere to a literal interpretation of the Bible. As a result, the reading of 1 Timothy 2:8-15 is misinterpreted. The main aim of this research is to reconstruct and present egalitarianization between women and men based on 1 Timothy 2:8-15, especially in the scope of worship services. It is still found that some churches reject women as priests. This research uses qualitative methods, with a critical historical approach. The results show that the Ephesian women were contaminated with a life of debauchery or a luxurious lifestyle, wanting to appear beyond their capacity. So they tend to ignore Christian values. So, it cannot be a measure to reject the existence of women as ministers of worship (pastor), only the church needs to pay attention to Christian values and foster them in Indonesia context.